Microcephaly as observed in the late 19th century cemetery of the Meerenberg psychiatric hospital: Diagnostic issues and the value of population‐specific data. (2nd December 2022) - Mank, Elise; de Boer, Hans H.; Versluis, Judith M.; Oostra, Roelof‐Jan; van der Merwe, Alie E.
Abstract: Microcephaly, characterized by crania with an abnormally small occipitofrontal circumference (OFC), is only sporadically described in paleopathological literature. Accurate identification of individuals suffering from microcephaly is challenging when performed in an archeological context, especially in mild cases, as appropriate reference data are often not available. This study aimed to describe the craniometric characteristics of the Meerenberg (MeB) skeletal collection and to identify microcephalic individuals while focusing on the diagnostic criteria and the influence of reference data on the prevalence of the condition. The value of virtual endocasts as a diagnostic tool was also assessed. Forty‐eight adults (1891–1936) excavated from the cemetery of the MeB psychiatric hospital (Bloemendaal, The Netherlands) were investigated. Microcephalic individuals were identified by using the craniometric characteristics of a contemporary Dutch archeological population as reference. In order to investigate the usefulness of modern clinical head circumference reference data on the diagnostic process, cranial OFCs of the MeB individuals were converted to head OFCs. Virtual endocasts were created from the identified microcephalics and three normocephalics. Three MeB females (all <−3 SD) were identified as microcephalic when compared with a sex‐matched contemporary archeological reference sample. The same three MeB females were classified as microcephalic when using sex‐matched modern clinical reference data and when applying −3 SD of the pooled sex archeological craniometric reference data as cut‐off point. No individuals were classified as microcephalic based on the metric characteristics of the virtual endocasts. Microcephaly can only be accurately identified when using sex‐matched contemporary population reference data, or in its absence, modern clinical data after soft tissue correction. Should sex estimation be unreliable, a –3 SD cut‐off point generated using pooled sex reference data seems suitable as diagnostic tool. Virtual endocast did not support the identification of microcephaly in this study.